PluMu—A Mu-like Bacteriophage Infecting Actinobacillus pleuropneumoniae - Lee Julia Bartsch; Roberto Fernandez Crespo; Yunfei Wang; Michael A. Skinner; Andrew N. Rycroft; William Cooley; David J. Everest; Yanwen Li; Janine T. Bossé; Paul R. Langford (Applied Microbiology, 2024)
Actinobacillus pleuropneumoniae is the causative agent of pleuropneumonia, an economically important lung disease in pigs. In draft genomes of two Cypriot clinical A. pleuropneumoniae isolates (MIDG3457 and MIDG3459), we previously identified single genomic regions with homology to Mu-like bacteriophage and presented preliminary evidence of active phage. Here, updated Phastest genomic analysis identified two loci in both MIDG3457 and MIDG3459 that were predicted to encode proteins with high homology to, and whose organisation was characteristic of, Mu-like phages. Phylogenetically, the closest matches were with Mannheimia Vb and Glaesserella SuMu phages. Phastest scored the loci as “complete”, indicating they produced active phage. PCR amplification of the Mu-like phage c and tail genes from DNase-treated polyethylene glycol 8000 (PEG)-precipitated supernatants of MIDG3457 and MIDG3459 (grown in either Brain Heart Infusion-NAD or Grace’s Insect Medium-NAD broth) indicated the presence of intact virions. The phages from MIDG3457 and MIDG3459 were named PluMu 3457-1, 3457-2, and PluMu 3459-1 and PluMu 3459-2, respectively. Transmission electron microscopy (TEM) of the PEG-precipitated supernatants of broth-grown MIDG3459 identified virions with icosahedral heads and tails, consistent with other Mu-like phages. We conclude that MIDG3459 produces an active Mu-like phage.